EXAMINING THE EFFECT OF DIRECTED ACTIVITY RELATED TO TEXTS (DARTs) AND GENDER ON STUDENTS’ ACHIEVEMENT IN QUALITATIVE ANALYSIS IN CHEMISTRY (Malaysian Journal of Learning and Instruction, 2021)
Purpose â€“ The present study examined the effect of Directed Activity Related to Texts (DARTs) and gender on student achievement in qualitative analysis in chemistry. It focused on the qualitative analysis component of the Chemistry course, which for students has been perceived as being the most difficult aspect of their mastery of the subject.Methodology â€“ The study involved 120 secondary four science stream students from two local fully residential schools. In a quasi-experiment, participants studied the topic of qualitative analysis of salt, using one of the following three instructional methods: Experiment, DARTs, and Combination of Experiment and DARTs. The participants in the three groups were then tested on their knowledge about salt. Findings â€“ Results of a two-way independent ANOVA performed on the experiment data revealed a significant main effect corresponding to the type of instructional method that the three groups were treated to â€” the mean scores for the Combined method group was the highest, followed by the DARTs group, and then the Experiment group. Further analysis using an independent t-test showed that the difference in mean scores between the DARTs and Experiment groups was significant. It is argued that participantsâ€™ learning in the Combined method group might have been enhanced by the DARTs instructional method. The effect of gender and the interaction effect between the variables were not significant.Significance â€“ The findings of the study has provided clear experimental evidence regarding the role of the DARTs instructional method in enhancing qualitative analysis learning in chemistry. These findings also provided important insights to educators on DARTs as an alternative method of teaching and learning the topic on qualitative analysis in chemistry.